Allocation of parts to cells, minimising tardiness and idle time by simulated annealing. (6th September 2005) - Tavakkoli-Moghaddam, R.; Rabbani, M.; Ghodratnama, A.; Ahmed, P.K.
This paper investigates an allocation of parts to common and specific cells and it also presents a mathematical programming model comprising of constraints such as available time for common and special cells in each time horizon, and variables such as excess time required by each cell to process parts in each period. The objective of the model is to minimise the total tardiness in production of goods and the sum of idle times of machines in each cell. Due to its complexity, a simulated annealing (SA) method is utilised. To verify the quality and efficiency of the SA algorithm, ten test problems with different parameter values are used to analyse and test the efficiency of the proposed SA method. Finally, results are compared with solutions obtained by Lingo 6 and computation time for each test problem.